A prospective study on clinical outcome of complicated external hernias (Health Renaissance, 2012)
Background: External hernias are relatively simple diseases in themselves to treat; however, complications developing in them, such as irreducibility, obstruction and strangulation, may present as a life-threatening one. Objective: To study the characteristics of these patients and identification of risk factors that may predict development of these complications would help place the patient in a high-risk group and subsequent intervention. Methods: It is a prospective descriptive study in patients presenting to Surgery Department of BPKIHS, Dharan, Nepal with a diagnosis of complicated external hernias from December 2009 to July 2011. Results: There were a total of 63 patients including 53 males (84.1%) and 10 females (15.8%). The average age of the patients was 49.23+21.4 years (range 10 days-85 years). The average duration of hernia was 6.36+6.57 years (range 5 hours -30 years). The median duration of complications was 2 days (range 5 hours-15 years). There were 7 mortalities (11.11%). The morbidity rate was 33.33% (21 cases). Risk factors identified for mortality were age >65 years (p=0.004), inguinal hernias (p